Managing and governing commodity chains: the role of producer service firms in the secondary global city of Hamburg - Parnreiter, Christof (DIE ERDE – Journal of the Geographical Society of Berlin, 2015)
This paper is motivated by the observation that our understanding of global cities in Germany and beyond is limited because the practices through which producer service firms (PSFs) are involved in managing and governing their clients’ global commodity chains (GCCs) have barely been studied. Based on interviews with representatives of PSFs in the secondary global city of Hamburg, the paper scrutinises whether and how service professionals contribute to the functioning and the control of their clients’ cross-border operations. It also analyses why clients choose global PSFs located in Hamburg, and it discusses which place Hamburg occupies in the network of German global cities. The paper concludes that because PSFs fulfil management functions for their clients’ global operations Hamburg is, beyond the role of its port, a critical node in many GCCs. Secondly, PSFs influence their clients’ decision-making processes. They are part of economic governance processes, though this impact cannot be straightforwardly equated with ‘command and control’. The paper also confirms that (and explains why) the world city network is the spatial correlate of a globalising economy. Finally, there is no such a thing as a ‘global city hierarchy’ because the division of labour between the offices of PSFs is functional. As regards further research, a first task is to verify this paper’s findings through interviews with clients of PSFs to consolidate our knowledge on the role of PSFs in GCCs. Secondly, the contention that the world city network is flat has to be re-examined against the backdrop of an evident clustering of PSFs in specific cities. Finally, the discussion of whether and how PSFs are involved in the governance of their clients‘ GCCs needs to be continued and deepened.